A novel buckling-restrained brace with auxetic perforated core: Experimental and numerical studies. (15th December 2021) - Zhang, Yi; Ren, Xin; Zhang, Xiang Yu; Huang, Ting Ting; Sun, Long; Xie, Yi Min
Highlights: A novel perforated negative Poisson's ratio core buckling-restrained brace (NP-BRB) was designed and manufactured. Seismic performance of the proposed buckling-restrained brace (BRB) was investigated. The proposed BRB with auxetic core has a desirable seismic property under cyclic loading. These findings have values in guiding the investigation and design of other metallic dampers regarding auxetics. Abstract: Auxetic materials could exhibit desirable mechanical properties, e.g., fracture resistance, shear resistance and energy dissipation due to their unique deformation characteristics. However, the seismic performance of auxetics in disaster prevention and mitigation of building structures is rarely studied. In this study, a novel perforated negative Poisson's ratio core buckling-restrained brace (NP-BRB) was designed and manufactured for exploring the hysteretic performance of auxetic metamaterials under cyclic load. Experiments and verified numerical simulations were conducted to investigate the effects of porosity and section weakening rate on the seismic performance. The results show that the NP-BRB has stable hysteretic curves and low compression strength adjustment factor. In addition, the parametric analysis indicated that the energy dissipation capacity of NP-BRB with relatively large section weakening rate could be improved due to auxetic behavior when the average strain exceeds 1%. These findings are beneficial to the applications of auxetic metamaterials in damping devices for mitigating seismic effects.